Unlocking the Stratum Corneum Barrier to Skin Penetration for the Transdermal Delivery of Cyclovirobuxine D - Yun-Hao Ren; Feng-Yuan Song; Jing-Yu Zhao; Bing-Wen Liang; Li-Hua Peng (Pharmaceutics)
Background/Objectives: Cyclovirobuxine D, a natural compound derived from the medicinal plant Buxus sinica, demonstrates a diverse array of therapeutic benefits, encompassing anti-arrhythmic properties, blood pressure regulation, neuronal protection, and anti-ischemic activity. However, its limited solubility hinders the bioavailability of current oral and injectable formulations, causing considerable adverse reactions and toxicity. Methods: In this investigation, we embarked on an unprecedented exploration of the skin penetration potential of cyclovirobuxine D utilizing chemical penetration enhancers and niosomes as innovative strategies to enhance its dermal absorption. These strategies were rigorously tested and optimized. Results: Among the tested chemical penetration enhancers, azone emerged as the most potent, achieving a 4.55-fold increase in skin penetration compared to the untreated group. Additionally, when encapsulated within niosomes, primarily composed of Span60 and cholesterol, the skin penetration of cyclovirobuxine D was notably enhanced by 1.50-fold. Furthermore, when both cyclovirobuxine D and azone were co-encapsulated within the niosomes, the skin penetration of cyclovirobuxine D was remarkably elevated by 8.10-fold compared to the solvent-dispersed group. This enhancement was corroborated through rigorous in vitro and in vivo experiments. Notably, the combination of other chemical penetration enhancers with niosome encapsulation also exhibited synergistic effects in enhancing the skin penetration of cyclovirobuxine D. Conclusions: These findings provide a compelling rationale for the administration of cyclovirobuxine D via skin-mediated transdermal delivery, offering superior safety, efficacy, and convenience. The innovative combination of niosomes and chemical penetration enhancers represents a novel system for the transdermal delivery of cyclovirobuxine D, holding immense promise for clinical applications in the treatment of brain, neuronal, and cardiovascular disorders.